Pertimbangan Harga dalam Keputusan Pembelian Skincare : Studi Kualitatif pada Konsumen Perempuan di Jakarta Selatan - Nurlianty Maharani Harahap; Michael Hidayat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to understand the considerations of female consumers in making decisions to purchase skincare products with the main focus on the price aspect. The background of this research is based on the increasing competition in the skincare market and the shift in consumer preferences for products that are not only judged by quality, but also by affordability. This study uses a qualitative approach with a case study method. The data was collected through in-depth interviews with six female informants who actively use skincare products and are domiciled in South Jakarta. The results show that perceptions of price are very diverse. Some consumers consider price as an indicator of quality, while others consider the economic value and effectiveness of the product more. Additionally, purchasing decisions are influenced by various factors such as income, skin needs, promotional strategies, and social media influence. In responding to prices, they also vary, ranging from waiting for promos to trying alternative brands that are more affordable. These findings reinforce Kotler and Keller's (2016) theory of personal and psychological factors in purchasing decisions, as well as being relevant to Monroe's theory of price perception. This research provides important implications for skincare business people in designing pricing and marketing strategies that are more adaptive to consumer behavior.